BEYOND SHARIA AND SECULARISM: Political Pluralism and Multiculturalism in the Concept of Dār al-Mīthāq - Musadad, Ahmad; Ramdlany, Ahmad Agus; Yasid, Yasid; Syaifudin, Mochamad (JOURNAL OF INDONESIAN ISLAM, 2025)
The relationship between religion and the state in Indonesia remains a perennial hot topic, never growing stale over time. This study examines the nexus between religion and the state through the lens of political pluralism and multiculturalism, focusing on the dār al-Mīthāq concept put forward by Ma’ruf Amin. The urgency of this research arises from Indonesia’s diverse socio-political dynamics and the threat of extremist ideologies endangering national unity. Employing a qualitative method with a normative-analytical approach, the study draws on library research and the analysis of both historical and contemporary documents. The findings demonstrate that dār al-mīthāq constructs a covenant-based constitutional framework that redefines the state as a religiously grounded consensus, integrating faith, justice, and tolerance within a plural society while simultaneously revealing its limitation as a form of normative multiculturalism that insufficiently addresses structural inequality and recognition gaps. These results underscore that applying the principles of political pluralism can serve as a strategic solution to ideological conflicts, while requiring a shift toward critical multiculturalism to ensure substantive equality and inclusive participation.